FUNGSI INTERJEKSI DALAM KUMPULAN CERPEN 100 TAHUN CERPEN RIAU - Ayu, Rahmatika Sari; Charlina, Charlina; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Interjection is a word that the writer uses to express the feelings and semosi characters. Interaction is commonly used in literary works such as short stories, novels, drama script, and film. This study aims to analyze the interjection function contained in the short story Cerpen Riau Cerpen Riau. The method used in this research is descriptive qualitative method with documentation technique. Sources of data in this study is the text of the Short Story Cerpen 100 Year Cerpen Riau which amounted to 100 short stories. The data in this study are sentences in which there are interjections. The results of this study suggest that 13 interjection functions with the number of functions expressing shock (31), expressing annoyance (20), expressing anger (4), expressing pain (2), expressing amazement (3), expressing mockery (3), (3), states call / greeting (12), states unbelief (6), states ignorance (7), states admiration (16), and states fear (5). Then the total usage of all functions is 113.Keywords: Interjection, Short Story, Some Story 100 Years Riau Short Story